Strength and small-strain modulus of lightweight geomaterials: cement-stabilised sand mixed with compressible expanded polystyrene beads. Issue 6 (1st December 2010) - Chiyoda, T.; Onishi, K.; Saito, R.; Tsukamoto, Y.
Abstract : ABSTRACT: The use of lightweight geomaterials for the construction of geotechnical structures is diverse. They are often used in the construction of embankments to reduce the bearing stress imposed on soft soil foundations. In particular, compressible small beads of expanded polystyrene (EPS) have become widely used, mixed with sandy soils and stabilised with cement. The reduction of weight due to the inclusion of such EPS beads is therefore beneficial. Nonetheless, such inclusion can degrade the fundamental strength and deformation properties of constructed geomaterials, even though they are stabilised with cement. In the present study, multiple series of triaxial compression tests were conducted using a pair of local deformation transducers (LDT), and the large-strain strength and small-strain modulus of cement-stabilised sands mixed with EPS beads were examined. The changes in the strength and deformation properties with increasing inclusion of EPS beads are examined and discussed in detail. Based on the outcome of the present study, the practical implications for design of lightweight geomaterials are also described.